Unpacking impacts of climate change and variability on agriculture, food security and incomes in Northern Uganda: A gender standpoint. Stakeholder opinions from seven districts in Northern Uganda - Bamanyaki, Patricia A.; Aogon, George (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This Info Note takes a gender standpoint to unpack and critically examine the impacts of climate change and variability on agricultural production, food security and incomes of farming households in Northern Uganda.